Kharif onion cultivation â€“ a boon for the farmers of Northern India - Sharma, Deepa; Banyal, Sanjeev K; Chauhan, Aanchal (Indian Horticulture, 2020)
The stored stock of rabi onion exhausts after November resulting in a critical gap in supply during November-January in North India. Therefore, we need to import onion from south India and other countries due to which price increases. The price of onion in North India goes up to â‚¹ 100-120 per kg during this period. So, if the farmers of North India go for cultivation of kharif onion, they will not only improve their livelihood by increasing their income but also contribute in steady supply of onion at reasonable price. Kharif onion production through setts must be popularized on a large scale to the farmers. In this technique, setts are produced in March-May and stored up to August. In the second fortnight of August, these setts are replanted in the fields which can be harvested from October to December as green or fully developed bulbs.